2022
DOI: 10.1172/jci.insight.159419
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting chemotherapy with low-dose decitabine through an immune-independent mechanism

Abstract: The DNA methyltransferase inhibitor decitabine has classically been used to reactivate silenced genes and as a pre-treatment for anti-cancer therapies. In a new variation of this idea, this study explores the concept of adding low-dose decitabine following administration of chemotherapy to bolster therapeutic efficacy. We find that addition of decitabine following treatment with the chemotherapy agent gemcitabine improves survival and slows tumor growth in a mouse model of high-grade sarcoma. Unlike prior stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Combining busulfan, melphalan, GEM and DAC inhibited lymphoma cell growth. Additionally, a recent study demonstrated that the combination of DAC and GEM inhibited osteosarcoma cell proliferation and retarded tumor growth (Gutierrez et al, 2022). We studied DAC and GEM's in vitro antiproliferative effects on NK92MI.…”
Section: Discussionmentioning
confidence: 99%
“…Combining busulfan, melphalan, GEM and DAC inhibited lymphoma cell growth. Additionally, a recent study demonstrated that the combination of DAC and GEM inhibited osteosarcoma cell proliferation and retarded tumor growth (Gutierrez et al, 2022). We studied DAC and GEM's in vitro antiproliferative effects on NK92MI.…”
Section: Discussionmentioning
confidence: 99%